Spiritual peace and new medicine. Impulses of Julian Aleksandrowicz - Alina Jagiełłowicz (Społeczeństwo, Edukacja, Język)
Social thought of Julian Aleksandrowicz is connected withthe expression “prevention of wars”. He looked at the problem of war from the perspective of potential sufferings and threat of extermintion of not only the humann world but also animate and inanimate environment. Julian Aleksandrowicz was convinced that peace is for the proper development of mankind what health is for human individuals. He stressed that in opposite to “scientific-technical” revolution, responsible for crises, the “scientific-ethical” resolution plays the basic role in prevention of wars. His concept made it clear that what should be asked bout is prevention of war in general, due to which the human will be able to recover above the limitations of anger, hatred, agression, destruction